ENHANCING STUDENTS’ LEXICAL RANGE THROUGH CORPUS LINGUISTICS: A CORPUS-BASED APPROACH TO VOCABULARY DEVELOPMENT - Yangiyeva Mohinur Asror qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Lexical range, defined as the breadth and diversity of vocabulary that learners can understand and use appropriately, is a critical component of second language proficiency. A limited lexical range often restricts learners’ ability to communicate effectively, comprehend authentic texts, and express complex ideas. Traditional vocabulary instruction frequently relies on memorization of isolated words, which may not adequately support long-term vocabulary growth. Corpus Linguistics offers an innovative approach by providing learners with access to authentic language data that illustrate how words are used in real contexts. This study explores the role of Corpus Linguistics in enhancing students’ lexical range through the use of the Corpus of Contemporary American English (COCA). Employing a qualitative corpus-based methodology, the study analyzes lexical patterns, collocations, synonyms, academic vocabulary, and phraseological units. The findings indicate that corpus-based learning promotes vocabulary expansion, contextual understanding, collocational competence, and learner autonomy. The study concludes that integrating corpus-based activities into English language teaching can significantly improve students’ lexical range and overall communicative competence.